Preparation of Primary School Teachers for Professional Activities for the Development of Mathematical Thinking of Younger Schoolchildren - Sokolov V.L (Moscow State University of Psychology and Education, 2022)
The article discusses one of the aspects of the training of a teacher of primary general education - the ability to analyze the causes of students' mistakes made by them when mastering mathematical concepts. The special importance in the competence of the primary school teacher of understanding the value of the initial, initial representations of the child as a result of his own mental activity is noted. An overview of the concept of mathematical thinking in the psychological and pedagogical literature is given. The understanding of mathematical thinking as theoretical, carried out on mathematical material, is highlighted. The levels of development of mathematical thinking and its main components - analysis, planning and reflection - are recorded. The modules of the educational program for the training of primary school teachers are described, aimed at developing students' competencies that allow them to adequately assess the manifestations of mathematical thinking in younger schoolchildren on mathematical material traditionally studied in primary school. The sequence of actions aimed at identifying the error pattern is presented. Examples of tasks for students are given, showing ways of developing the educational action of control; determining patterns of mathematical errors.